Intragenic NF1 deletions in sinonasal mucosal malignant melanoma. (8th October 2021) - Riobello, Cristina; Casanueva Muruais, Rodrigo; Suárez‐Fernández, Laura; García‐Marín, Rocío; Cabal, Virginia N.; Blanco‐Lorenzo, Verónica; Franchi, Alessandro; Laco, Jan; López, Fernando; Llorente, José Luis; Hermsen, Mario A.
Abstract: Mucosal malignant melanoma (MMM) is a rare and aggressive tumor. Despite effective local therapies, tumor recurrence and metastasis remain frequent. The genetics of MMM remain incompletely understood. This study is aimed to identify actionable genetic alterations by next‐generation sequencing. Fifteen MMM samples were analyzed by next‐generation and Sanger sequencing. Gene copy number alterations were analyzed by MLPA. Mutation status was correlated with pERK, pAKT, and Ki‐67 expression and follow‐up data. Inactivating mutations and intragenic deletions in neurofibromatosis type‐1 ( NF1) were identified in 3 and 2 cases, respectively, (in total 5/15, 33%) and activating mutations in NRAS and KRAS (3/15, 20%) cases. Other mutated genes included CDKN2A, APC, ATM, MITF, FGFR1, and FGFR2 . BRAF and KIT mutations were not observed. Cases with NF1 alterations tended to have worse overall survival. The mutational status was not associated with pERK, pAKT, or Ki‐67 immunostaining. MMM carries frequent gene mutations activating the MAPK pathway, similar to cutaneous melanoma. In contrast, NF1 is the most frequently affected gene. Intragenic NF1 deletions have not been described before and may go undetected by sequencing studies. This finding is clinically relevant as NF1 ‐mutated melanomas have worse survival and could benefit from therapy with immune checkpoint and MEK inhibitors.